Primary Pulmonary Synovial Sarcoma: A Case with Unique and Impressive Computed Tomography Findings - Jaspreet S Kambo; Bonnie Richardson; Diana N Ionescu; Tracy Tucker; Greg Kraushaar (Canadian Respiratory Journal)
Primary pulmonary synovial sarcoma (PPSS) is a rare malignancy. Its etiology, imaging features and optimal treatment are not well understood. Pulmonary pseudoaneurysms and lymphadenopathy are rare complications of synovial sarcomas. A 40-year-old woman with mild hemoptysis and thoracic back pain underwent a computed tomography scan that revealed multiple pulmonary lesions, paraesophageal lymphadenopathy and incidental bilateral pulmonary emboli. A diagnosis of PPSS was made through the identification of an SS18 translocation by fluorescence in situ hybridization. She was started on adriamycin, ifosfamide and mesna chemotherapy. Over the subsequent two months, she developed three pulmonary artery pseudoaneurysms, ultimately requiring endovascular coiling. Seven months after starting treatment, the patient was asymptomatic. The lesions and lymphadenopathy decreased in size. The present case highlights complications of a rare malignancy and demonstrates positive response to ifosfamide-based chemotherapy in the setting of PPSS.